Planning For The Number Of Optimal CPO Production Using The Goal Programming Method At PT.Socfindo Kebun Seunagan's Palm Oil Mills - muhammad - sangkot; Gaustama Putra (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
In good management, planning is very influential in implementing production activities. Production planning in the factory is carried out based on the estimated production of crude palm oil (CPO) and Palm Kernel Oil (PKO) for each period. This estimate uses production data in the previous period. But in reality, companies are often confronted with conditions where there is a mismatch of production with the volume of planned production targets. The method used as an optimal solution to determine CPO production is the goal programming method. Data processing is carried out by predicting demand and then processed with LINDO's ( linear interactive discrete optimizer). The decision variable is based on the factory's CPO production activities and FFB procurement activities. The target to be achieved from this study is to obtain an optimal production plan as an alternative problem-solving in optimizing unemployed production capacity. The optimal production results are accepted by the goal programming approach for the next period to be the 7th period 362981,875 kg, the 8th period 353489 kg, period-9 301006 kg, period-10 271630, kg, period-11 350043,562 kg, period 12 335153,281 kg. Thus it can be said that the total demand can be fulfilled. The results of comparing forecasting demand and data processing with the goal programming method, production is declared optimal because production can be met.